Sex Determination of Sea Cucumber Acaudina rosettis from Madura Straits, Indonesia - Winarni, Dwi; Lestari, Lita I.D.; Hayati, Alfiah; Nabilla, Nithasya; Khaleyla, Firas (Universitas Negeri Surabaya, 2022)
Acaudina rosettis is one of the commercial sea cucumber species that is widely consumed on the east coast of Surabaya, East Java, Indonesia. Although its abundance in nature has begun to show signs of decreasing, studies on this species are still very limited. This study aimed to examine indicators that can be used to determine the sex of A. rosettis individuals. Acaudina rosettis samples were collected from Madura strait in the mid of Hijri month for three months. The sea cucumber samples were then dissected. Body wall without viscera and gonads was weighed. The gonads were then characterized macroscopically and microscopically, prepared into histological slides with hematoxylin-eosin staining. The results showed that A. rosettis samples could be classified into three sex groups based on the type of gamete cells observed in the tubules; male (spermatogenic), female (oogenic), and undetermined sex (no gamete cells found). Gonads had three colors; yellow, pink, and orange and were in five stages of reproductive phase; gametogenesis (G), mature (M), spawning (S), and post-spawning (PS). Male samples had yellow and orange gonads, female samples were pink and orange, and all undetermined sex were orange. The G gonads were yellow and orange, M were yellow and pink, while S and PS were orange. Body wall and gonad weight at the same reproductive phase did not show any difference between males and females. Based on the results, gonad color can be used as an indicator of sex determination, but only in G and M reproductive phases.